INTEGRASI PENDIDIKAN NILAI DALAM MEMBANGUN KARAKTER SISWA DI SEKOLAH DASAR JAMPALAN KECAMATAN SIMPANG EMPAT KABUPATEN ASAHAN PROVINSI SUMATERA UTARA - Intan Kumala Sari; Luciana Nasution; Candra Wijaya (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Value education is a system of building character values or school citizens which includes the components of knowledge, awareness or willingness, and actions to implement these values to God Almighty, oneself, others, environment, and nationality so that they become human beings who are qualified for their morals. After conducting research and interviews with several teachers, the researcher draws the conclusion that in terms of delivering value education in schools for Elementary Schools, the teacher uses a contextual learning approach model that is the effort of educators to connect the material taught with the real world situation of students, encouraging students make connections between the knowledge they have and their application in their lives as family members and communities. The learning system adopted in Jampalan Elementary School is inseparable from the existence of Asahan district Government No.19 of 2005 concerning National Education Standards and the Vision namely